If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 8 = 13x + 14 Reorder the terms: 8 + 10x = 13x + 14 Reorder the terms: 8 + 10x = 14 + 13x Solving 8 + 10x = 14 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 8 + 10x + -13x = 14 + 13x + -13x Combine like terms: 10x + -13x = -3x 8 + -3x = 14 + 13x + -13x Combine like terms: 13x + -13x = 0 8 + -3x = 14 + 0 8 + -3x = 14 Add '-8' to each side of the equation. 8 + -8 + -3x = 14 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 14 + -8 -3x = 14 + -8 Combine like terms: 14 + -8 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| (x-7)-(x+6)=9x | | 2y-1/-3=5 | | A+4a=30 | | 9w^2-24w+16=0 | | -3.9=2.6+1.3y | | 8n+5m=-13 | | x/0.45-2.5=-3 | | 12+9-2m-16= | | 8n-24= | | -3.9=2.6+1.33 | | 20t-t^2=0 | | 7(1.5)+x=25.45 | | -3(x+2)+5x=8 | | g(x)=4x^2-12x+9 | | 24=k+22+9k+2 | | 8xn+y=54 | | -3(7n+1)=45 | | -11t=1s-6t | | 15.95=3.19n | | 2(3x-1)+4=-20 | | 1+3x=8a+6 | | 15.95=3.19 | | 2(8y-11)-7=147 | | g+11=9 | | 20-3x-2x= | | 8y+x=13x+20 | | 2(x-y)+3(x-y)= | | 9x+8.32=7x+11 | | 6x-2+4=-20 | | 19/5=5k/5 | | -5.8+1.1x=4.5 | | 123=3x-3 |